The need to review low-dose decision-making in radiation protection. (12th January 2022) - Coates, Roger
Abstract: The current approach in the system of protection, and the way in which it is implemented in regulation and practical application, has resulted in the allocation of significant and disproportionate societal resources to reduce relatively low-level exposures to even lower levels. The resulting exposure levels are often a fraction of the basic natural background level, and in particular are comparable to, or often significantly less than, the variability of natural background exposures due to individual decision-making, which the system of protection deems acceptable. There are arguments for a wider approach to decision-making at such low doses, recognising the uncertainties in radiation risk estimation and acknowledging the context that all human life takes place in a variable natural background radiation which generally dominates these lower dose exposures. Recommendations are presented for improvements in how decisions are made in controlling low doses.